An introduction to exercise metabolism 1 - Gleeson, Michael (Henry Stewart Talks, 2021)
Energy, Energy metabolism and the role of adenosine triphosphate (ATP), Energy sources for high-intensity exercise like sprinting, Energy provision for prolonged moderate-intensity exercise, Fat as a fuel for exercise